Live Streaming TikTok Sebagai Strategi Komunikasi Pemasaran Pada Brand Skincare - Jacob, Delicia Regina (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research investigates using TikTok live streaming as a creative marketing communications strategy in the skin care industry. The research method used is descriptive qualitative with a basis in marketing communication theory and new media concepts. Through interviews and focus group discussions, this research explores how the skincare brand "Skintific" utilizes TikTok's live streaming feature to expand the market and increase sales. The research results show that Skintific has successfully integrated live streaming with a marketing communications mix, such as advertising, promotions, personal sales, and direct marketing, creating interactions that positively impact the audience. These findings underscore the importance of adapting to new trends in social media as an integral part of an effective marketing strategy. The practical implication of this research is to provide insight for marketing practitioners in optimizing live streaming as a powerful and impactful communication tool in modern marketing. In conclusion, the use of TikTok live streaming is a potential and relevant strategy to increase consumer engagement and expand market reach for skin care brands and similar industries. By taking advantage of new features on TikTok, such as live streaming, personal selling adjustments, relevant communication approaches, effective click-to-action, product layout, right pricing, and discounts, Skintific recorded significant growth from 2021 to the moment.